Juridical Review of the Spread of Pinkflash Dangerous Cosmetics in the Perspective of Legal Protection of Consumers in Indonesia - Ketut Purnama Sari; I Nyoman Bagiastra (Sociological Jurisprudence Journal, 2025)
The development of the times and the advancement of technology, namely social media, causes someone to want to look beautiful, especially for women. This can be seen by the many transactions of buying and selling various cosmetic products either through direct shopping to the store or using applications such as Shopee and Tokopedia online. Some cosmetic products on the market contain harmful substances. These cosmetics are certainly dangerous if applied to facial skin.  The most fatal negative impact can cause cancer or damage to facial skin. The purpose of writing this journal is so that women or other consumers are more sensitive and vigilant in choosing and using cosmetics on the market. The writing method used is normative legal research, with a legal approach, cases and reviewing secondary legal materials as the main data source. The problem in this study is how to protect consumers due to the spread of cosmetics from pinkflash products that contain harmful ingredients. The results of the study found that several types of cosmetics from the Pinkflash brand contain harmful substances. This product is known to have spread widely in the market, so it is important to do several strategic ways through the UUPK and the Health Law in resolving risks. The form of legal protection provided is in the form of preventive and repressive protection.